Peran Kejaksaan dalam Perampasan Aset dalam Pemberantasan Tindak Pidana Korupsi Serta Kendala Yang Dihadapi dalam Pelaksanaannya - Yohanes, Yohanes; Danil, Elwi; Mulyati, Nani (UNES Law Review, 2023)
This research is motivated by the lack of optimal eradication of criminal acts of corruption in Indonesia, which is indicated by data showing that the value of state financial losses in criminal acts of corruption that have been handled cannot be recovered by law enforcement. This issue is a challenge in eradicating criminal acts of corruption, not only imprisoning the perpetrators of corruption but more than that, how to confiscate the assets of the perpetrators of corruption as far as possible and return them to the state. Based on data released by ICW, the handling of criminal acts of corruption has not been followed by optimal asset recovery, including that carried out by the Prosecutor's Office. Using empirical juridical methods, this research concludes that the Prosecutor's Office has a very important role in carrying out Asset Confiscation in eradicating criminal acts of corruption, both as investigators, public prosecutors and as State Attorneys. However, this role cannot be carried out optimally by the Prosecutor's Office, especially in the regional level, in this case the High Prosecutor's Office and the District Attorney's Office, are still experiencing various obstacles. in implementation.